Characterizing difficulties with emotion regulation in toddlers with autism spectrum disorder. (August 2022) - Day, Taylor N.; Mazefsky, Carla A.; Wetherby, Amy M.
Abstract: Background: Difficulties with emotion regulation (ER) underlie emotional/behavioral challenges and co-occurring psychiatric symptoms in autism spectrum disorder (ASD), yet very little is known about the early development of emotion dysregulation. The present study aimed to identify differences in positive and negative emotional reactivity and regulation strategies in toddlers with and without ASD. Method: Nine tasks from the Laboratory Temperament Assessment Battery (Lab-TAB) were completed with 37 toddlers with and without ASD (22–28 months). Video-recordings of these tasks were coded by research assistants using a behavioral coding scheme tapping facial, bodily, and vocal affect and the frequency of ER strategies. Mixed model analyses were performed to examine the mean affect and total regulation strategies across each task and t-tests were conducted to assess the types of ER strategies utilized. Results: Toddlers with ASD showed significantly less positive affect and greater frustration compared to non-ASD toddlers; reactivity was comparable between the groups for fear. Both groups used ER strategies in a similar pattern across tasks, with the exception that toddlers with ASD more often engaged in distraction to regulate. Effects of age and developmental level are discussed. Conclusions: Toddlers with ASD were robustly characterized by greater frustration and lower joy despite frequent and age appropriate attempts to regulate their emotions. This study provides preliminary evidence that observable indicators of emotion dysregulation are present by two years of age. Clinical implications and future research directions are discussed. Highlights: Emotion dysregulation underlies emotional/behavioral challenges in ASD. Toddlers with ASD demonstrate more frustration and less joy than non-ASD toddlers. Toddlers with ASD utilize emotion regulation strategies ineffectively. Observable indicators of emotion dysregulation are present by two years of age. Early childhood may be an ideal window to intervene on emotion dysregulation.